Production of Carbohydrates from Cardoon Pre-Treated by Acid-Catalyzed Steam Explosion and Enzymatic Hydrolysis - Alessandro Bertini; Mattia Gelosia; Gianluca Cavalaglio; Marco Barbanera; Tommaso Giannoni; Giorgia Tasselli; Andrea Nicolini; Franco Cotana (Energies, 2019)
Cardoon (Cynara cardunculus) is a promising crop from which to obtain oilseeds and lignocellulosic biomass. Acid-catalyzed steam explosion is a thermochemical process that can efficiently pre-treat lignocellulosic biomass. The drawback is the production of a high number of carbohydrate degradation products in the liquid fraction that could inhibit microbial growth. In this work, the lignocellulosic biomass of cardoon, gathered from a dedicated field, were used as the raw material for the production of fermentable monosaccharides by employing acid-catalyzed steam explosion. The raw material was pre-soaked with a dilute 1% (w/w) sulfuric acid solution and then subjected to steam explosion under three different severity conditions. The recovered slurry was separated into solid and liquid fractions, which were individually characterized to determine total carbohydrate and inhibitor concentrations. The slurry and the washed solid fraction underwent enzymatic hydrolysis to release glucose and pentose monosaccharides. By conducting the pre-treatment at 175 °C for 35 min and hydrolyzing the obtained slurry, a yield of 33.17 g of monosaccharides/100 g of cardoon was achieved. At the same conditions, 4.39 g of inhibitors/100 g of cardoon were produced.